Pengaruh Stressful Life Event terhadap Kecenderungan Non-Suicidal Self-Injury yang Dimediasi oleh Sensation Seeking pada Remaja SMA Negeri di Batu - Rosheila Bety Destian; Awaludin Ahya; Dwi Yulis Susanto; Mohamad Iksan (Yayasan Literasi Sains Indonesia, 2025)
This study aims to determine the effect of stressful life events on the tendency of non-suicidal self-injury mediated by sensation seeking in high school students in Batu. The type of research used in this study is a quantitative method approach. The study population was adolescents registered in 2024/2025, with a minimum sample of 115 people taken using a purposive sampling technique. The subjects in this study were high school students in Batu aged 15-18 years who experienced stress in their daily lives and had a tendency to hurt themselves without the intention of committing suicide. The instrument used for data collection in this study was a questionnaire arranged according to the Likert scale model. Data analysis was carried out in this study using statistical programs on SPSS 27.0 and Microsoft Excel computers. The results of this study indicate 1) There is a significant influence between stressful life events on the tendency of non-suicidal self-injury; 2) There is a significant influence between sensation seeking on the tendency of non-suicidal self-injury; 3) There is a significant influence between stressful life events on sensation seeking. Therefore, all hypotheses in this study are accepted.